Analysis of studies on Time-Driven Activity Based Costing (TDABC) - Alex Santana; Paulo Afonso (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The present article is part of a line of research based on the study, development and application of new approaches at the level of Strategic Cost Management (SCM), cost management and costing systems. Time-Driven Activity Based Costing (TDABC) which, in turn, represents the current level more sophisticated in terms of costs management systems and costing. A literature review on TDABC was conducted with the main objective of identifying the studies that have applied this model and check for new theories combined with TDABC. The research can be classified as archival analysis, qualitative and exploratory consisting of articles on TDABC. The results are based on 14 studies that applied the model, and 6 research papers with complementary joint approaches to TDABC.
Keywords: 650; Strategic Cost Management; Time-Driven ABC; Archival Research Method